Nutrition and Chronic Conditions - Omorogieva Ojo (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The effects of nutrition in chronic conditions, such as diabetes, cardiovascular disease, dementia, stroke, and inflammatory bowel disease continue to generate interest among researchers. This stems from the fact that diet is a modifiable risk factor for these diseases, which manifest either as single entities or in co-morbid states in individuals and populations around the world. In particular, the prevalence of diabetes and cardiovascular disease is on the rise, especially in developed countries, but also in developing economies, partly due to lifestyle changes, including diet. For example, ischaemic heart disease is the leading cause of death globally. When combined with stroke, these conditions accounted for 15 million deaths in 2015 and are the world's greatest killers (WHO, 2017). Furthermore, WHO (2016), reported that there were an estimated 422 million adults who were living with diabetes in 2014. This is significantly higher than the 108 million in 1980, representing a rise in worldwide diabetes prevalence from 4.7% in 1980 to 8.5% in 2014 among the adult population. These chronic conditions and their associated complications have significant implications for morbidity and mortality, and incur huge costs to the health services around the world. The composition of the diet, the proportion and types of macronutrients and micronutrients present in the diet are major contributors to these diseases. In addition, the beneficial effects of nutritional interventions have been well documented although differences remain among researchers with respect to their overall impact. The evaluation of the role of nutrition in chronic conditions draws on its effect on body weight and body composition, glycaemic and insulin excursions, vascular remodeling, and gastro-intestinal dysfunction. Therefore, this Special Issue on "Nutrition and Chronic Conditions" aims to evaluate the effect of nutrition in the development, care, and management of chronic conditions. The primary conditions of interest are diabetes, cardiovascular disease, dementia, stroke, and inflammatory bowel disease.